2020
DOI: 10.1177/0891988720958542
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Usual Cognitive Screening Tests Versus Appropriate Tests for Lower Education to Identify Alzheimer Disease

Abstract: Introduction: The accuracy of commonly used screening tests for Alzheimer’s disease (AD) has not been directly compared to those that could be more appropriate for lower schooling. Objective: To compare the diagnostic accuracy of usual screening tests for AD with instruments that might be more appropriate for lower schooling among older adults with low or no literacy. Methods: The study included a clinical sample of 117 elderly outpatients from a Geriatric Clinic classified as literate controls (n = 39), illit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…This suggestion is an old one 5 and has been supported by several studies, including two by one of the signers of the letter. 6 , 7 Interestingly, Ortega et al 6 directly compared tests included in the BCSB and the CNTB and stated that “data from the present study suggest that the use of colored stimuli seems to be a relevant strategy in the evaluation of memory among people with low schooling, as they may facilitate encoding.” It is noteworthy, that the name of the RPT was changed to the “Colored Figure Memory Test” in this publication.…”
mentioning
confidence: 74%
“…This suggestion is an old one 5 and has been supported by several studies, including two by one of the signers of the letter. 6 , 7 Interestingly, Ortega et al 6 directly compared tests included in the BCSB and the CNTB and stated that “data from the present study suggest that the use of colored stimuli seems to be a relevant strategy in the evaluation of memory among people with low schooling, as they may facilitate encoding.” It is noteworthy, that the name of the RPT was changed to the “Colored Figure Memory Test” in this publication.…”
mentioning
confidence: 74%
“…The high prevalence of lower educational achievement and socioeconomic disparities in LAC could explain the lowest performance of loweducated individuals on neuropsychological tests and contribute to misdiagnosis (50,51). In these population, the di culties of employing diagnostic batteries requires cultural adaptation of neuropsychological instruments considering cognitive skills predominantly used in the daily context of life is essential to understanding the cognitive skills of learning and information management, and, consequently, to identifying pathologic cognitive impairment (52).…”
Section: Discussionmentioning
confidence: 99%
“…35,36 These abilities also decline in non-demented elderly individuals so CP copying is not as sensitive for discriminating AD from non-demented elderly individuals. 37 Clinically, verbal cognitive tests are most used in evaluation of memory. Studies suggested difficulty retrieval words confound performance on verbal cognitive measures and may lead to the impression of memory impairment.…”
Section: Discussionmentioning
confidence: 99%
“… 35 , 36 These abilities also decline in non-demented elderly individuals so CP copying is not as sensitive for discriminating AD from non-demented elderly individuals. 37 …”
Section: Discussionmentioning
confidence: 99%